Hubungan Pijat Aromaterapi Minyak Atsiri terhadap Produksi Asi dan Stres pada Ibu Postpartum - Dian Fitriana; Ratna; Feri Catur Yuliani (Prodi Keperawatan Purwokerto, Poltekkes Kemenkes Semarang, 2025)
Background: Breast milk (ASI) production and maternal stress are two interrelated factors that influence the postpartum period. This study aimed to examine the correlation between aromatherapy massage using lavender essential oil and breast milk production as well as stress levels among postpartum mothers. Objective: This quasi-experimental study employed a pretest-posttest control group design involving 30 postpartum mothers in Siti Hajar Ward at Sultan Hadlirin Islamic Hospital Jepara. Methods: The sample was divided into an intervention group, which received aromatherapy massage with lavender essential oil for three consecutive days, and a control group. Data were collected using a breastfeeding observation sheet and the Perceived Stress Scale (PSS-10). Results: The results showed that 80% of mothers in the intervention group experienced increased breast milk production and reduced stress levels, while only 40% of mothers in the control group reported increased breast milk production. Chi-Square test results indicated a significant correlation between aromatherapy massage and improvements in both outcomes (p < 0.05). Conclusion: Conclusion Aromatherapy massage with lavender essential oil is effective in enhancing breast milk production and reducing stress, making it a potential complementary therapy in maternal health care.